Perancangan Website Yayasan Panti Asuhan Mekar Lestari - Ignatius Adrian Mastan; Melvina Sesilia (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2022)
The development of information technology has brought many positive impacts on society. One of the most felt impacts is the use of the website. Websites can help provide information about an organization. The organization can be a profit oriented organization or a non profit oriented organization. One organization that requires the use of a website is the Mekar Lestari Orphanage Foundation. The Mekar Lestari Orphanage Foundation is located in the Rawa Buntu area, Tangerang. The Mekar Lestari Orphanage Foundation houses about 80 orphans. The Mekar Lestari Orphanage Foundation has always relied on donations from the surrounding community for their daily needs and activities at the orphanage. The Mekar Lestari Orphanage Foundation so far in recording donations and orphanage activities as well as managing orphans still uses the manual method, so it is difficult to provide information to donors to find out activities in the orphanage, as well as the limited information that can be known by the public about the orphanage. With the design of the Mekar Lestari Orphanage Foundation's website, it can help the community (donors) in making donations, as well as regarding various activities and data regarding orphans sheltered by the Mekar Lestari Orphanage Foundation. This website design will use the PHP and HTML programming languages. It is hoped that this website will make it easier for people (donors) to make donations, and help the Mekar Lestari Orphanage Foundation to manage and provide information related to activities at the Mekar Lestari Orphanage Foundation.